Decompressive Craniectomy vs. Craniotomy Only for Traumatic Brain Injury: A Propensity-Matched Study of Long-Term Outcomes in Neuropsychology - Guo, Zhengqian; Ding, Wantao; Cao, Dan; Chen, Yong; Chen, Jian (Frontiers in Neurology, 2022)
Background Both decompressive craniectomy (DC) and craniotomy only (CO) are commonly performed to treat patients with traumatic brain injury (TBI) by evacuation of intracranial hemorrhage (ICH) and control intracranial pressure (ICP). The outcomes of these two procedures have been well-studied; however, most research studies have focused on physical functions. The purpose of our study is to assess long-term outcomes in neuropsychology after DC or CO in TBI patients. Methods Information was collected from patients with TBI who had undergone DC or CO and were then in the postoperative stable phase (6–24 months after injury). Propensity scoring matched the patients in a 1:1 ratio for demographics, cause of injury, TBI subtype, TBI severity, computed tomography (CT) findings, surgery side, and interval from TBI. We used Wechsler Adult Intelligence Scale-Chinese Revision (WAIS-RC), Wechsler Memory Scale-Chinese Revision (WMS-RC), Physical Self-maintenance Scale (PSMS), Instrumental Activities of Daily Living Scale (IADL), and Glasgow Outcome Scale-Extended (GOSE) to measure the long-term outcomes in TBI patients, especially in neuropsychology. Results There were 120 TBI patients included in our study. After matching, 74 patients were paired into the DC group (n = 37) and the CO group (n = 37). There were no differences in the gender (P = 1.000), age at injury (P = 0.268), marital status (P = 0.744), pre-injury employment (P = 0.711), comorbidities (P = 1.000), education level (P = 0.969), cause of injury (P = 0.357), TBI subtype (P = 0.305), Glasgow Coma Scale (GCS) total score (P = 0.193), unconsciousness (P = 0.485), traumatic subarachnoid hemorrhage (tSAH) (P = 0.102), unresponsive pupil (P = 1.000), midline shift (P = 0.409), cisterns compressed or absent (P = 0.485), surgery side (P = 0.795), and interval from TBI (P = 0.840) between the two groups. The CO group was associated with better cognitive function in WAIS-RC OIQ (P = 0.030) and WAIS-RC FIQ (P = 0.021) and better daily function in IADL (P = 0.028) and ADL total (P = 0.030). The DC group also had a lower GOSE (P = 0.004) score compared to the CO group. No difference was observed in WAIS-VIQ (P = 0.062), WMS-RC MQ (P = 0.162), and PSMS (P = 0.319). Conclusion In the matched cohort, patients who underwent CO had better long-term outcomes in cognitive and daily function compared with DC. Future randomized control trials are needed for intensive studies on physical and neuropsychological prognosis in TBI patients.